2024
DOI: 10.1021/acs.macromol.3c01826
|View full text |Cite
|
Sign up to set email alerts
|

Smoother Surfaces Enhance Diffusion of Nanorods in Entangled Polymer Melts

Phillip A. Taylor,
Jiuling Wang,
Ting Ge
et al.

Abstract: Coarse-grained molecular dynamics simulations are used to study the diffusion of thin nanorods in entangled polymer melts for varying nanorod length and roughness. While prior studies observed a nanorod parallel diffusion constant scaling inversely with rod length D ∥ ∼ l −1 , here, we show that this scaling is not universal and depends sensitively on the nanorod surface roughness. We observe D ∥ ∼ l −k , where k < 1 and decreases with decreasing surface roughness. The weaker scaling is driven by the non-Gauss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…For spherical nanoparticles of diameter ( d NP ) smaller than the polymer characteristic length scales, the SE relationship underestimates the nanoparticle diffusivity because the particle dynamics is only coupled with the relaxations of local segments of polymer chains of size on the order of d NP . ,, While when the particle size is lightly larger than the mesh size of polymer entanglements ( d NP ≈ 1–10 d T ), the particles are still able to move faster than the SE estimation since they can transport through the local fluctuations of entanglements (the constraint release mechanism) , or by hopping when a gate (loop) between two neighboring confinement cages fluctuates to become large enough to slip around the particle (the hopping mechanism). Likewise, the diffusion of rod-shaped particles in polymer systems should also depend on the geometric parameters of the rods with respect to the length scales of the polymers. Indeed, it has been examined by both experiments and simulations and found that the diffusivity of NRs in polymer melts is higher than that predicted by the continuum theory; ,,,, however, the shape anisotropy makes their behavior quite different from that of spherical particles.…”
Section: Introductionmentioning
confidence: 99%
“…For spherical nanoparticles of diameter ( d NP ) smaller than the polymer characteristic length scales, the SE relationship underestimates the nanoparticle diffusivity because the particle dynamics is only coupled with the relaxations of local segments of polymer chains of size on the order of d NP . ,, While when the particle size is lightly larger than the mesh size of polymer entanglements ( d NP ≈ 1–10 d T ), the particles are still able to move faster than the SE estimation since they can transport through the local fluctuations of entanglements (the constraint release mechanism) , or by hopping when a gate (loop) between two neighboring confinement cages fluctuates to become large enough to slip around the particle (the hopping mechanism). Likewise, the diffusion of rod-shaped particles in polymer systems should also depend on the geometric parameters of the rods with respect to the length scales of the polymers. Indeed, it has been examined by both experiments and simulations and found that the diffusivity of NRs in polymer melts is higher than that predicted by the continuum theory; ,,,, however, the shape anisotropy makes their behavior quite different from that of spherical particles.…”
Section: Introductionmentioning
confidence: 99%